1989
DOI: 10.1002/cyto.990100605
|View full text |Cite
|
Sign up to set email alerts
|

Statistical evaluation of cell kinetic data from DNA flow cytometry (FCM) by the EM algorithm

Abstract: Flow cytometric DNA measurements yield the amount of DNA for each of a large number of cells. A DNA histogram normally consists of a mixture of one or more constellations of GdG,-, S-, G2/Mphase cells, together with internal standards, debris, background noise, and one or more populations of clumped cells. We have modelled typical DNA histograms as a mixed distribution with Gaussian densities for the Go/G1 and G2/M phases, an S-phase density, assumed to be uniform between the Go/G1 and G2/M peaks, observed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(46 citation statements)
references
References 33 publications
0
46
0
Order By: Relevance
“…In the present series, tumours of malignancy grades I and II were more common (28% vs 20% in the database), as were Ortho 50 H cytofluorograph (Baldetorp et al, 1989).…”
Section: Materials and Methods Patientsmentioning
confidence: 43%
“…In the present series, tumours of malignancy grades I and II were more common (28% vs 20% in the database), as were Ortho 50 H cytofluorograph (Baldetorp et al, 1989).…”
Section: Materials and Methods Patientsmentioning
confidence: 43%
“…Falsely low SPF values in diploid tumours might also explain the parabolic shape of the survival curve -indeed it was found that the non-linear (parabolic) shape was to some extent restricted to diploid tumours (P = 0.07). We are currently developing methods of measuring the SPF with greater precision, using statistical methods to adjust for background debris (Baldetorp et al, 1989). Also of particular interest are tumours with low SPF values and these should be analysed more thoroughly -we will be using tumour imprints and image (static) cytometry to investigate to what extent tumour cells are mixed with normal cells, and if possible to estimate the corrected SPF values of such tumours.…”
Section: Discussionmentioning
confidence: 99%
“…The specimens were stored frozen (-70°C), and later analysed (in a single laboratory) at the Oncology Department in Lund. Flow cytometry as described in detail elsewhere (Baldetorp et al, 1989) was performed on about 100-200 mg of tumour tissue thawed in 100-200 ,4 of citrate buffer (sucrose 250 mM, trisodium citrate 40 mm and dimethylsulphoxide 5%, pH 7.6) containing chicken (CRBC) and trout (TRBC) red blood cells, i.e. approximately 106 cells ml-' (Vindelov et al, 1983).…”
Section: Methodsmentioning
confidence: 99%
“…Staining of nuclei and¯ow cytometric analysis were performed as previously described (Baldetorp et al, 1989(Baldetorp et al, , 1992. Brie¯y, for staining of nuclei, cells were washed in PBS (phosphate bu er saline), whereupon nuclei isolation medium containing propidium iodide was added.…”
Section: Determination Of Cell Cycle Distribution By¯ow Cytometric Dnmentioning
confidence: 99%